2015
DOI: 10.1016/j.jprot.2015.03.037
|View full text |Cite
|
Sign up to set email alerts
|

Important mitochondrial proteins in human omental adipose tissue show reduced expression in obesity

Abstract: a b s t r a c tObesity is associated with impaired mitochondrial function. This study compares mitochondrial protein expression in omental fat in obese and non-obese humans. Omental adipose tissue was obtained by surgical biopsy, adipocytes were purified and mitochondria isolated. Using anion-exchange chromatography, SDS-PAGE and mass-spectrometry, 128 proteins with potentially different abundances in patient groups were identified, 62 of the 128 proteins are mainly localized in the mitochondria. Further quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 37 publications
(5 reference statements)
1
18
0
Order By: Relevance
“…Supplementary Table 1 contains a list of all 126 proteins found and includes also proteins of non-mitochondrial origin. Supplementary Table 2 contains all 62 mitochondrial proteins with potentially different abundance [1] .…”
Section: Data Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Supplementary Table 1 contains a list of all 126 proteins found and includes also proteins of non-mitochondrial origin. Supplementary Table 2 contains all 62 mitochondrial proteins with potentially different abundance [1] .…”
Section: Data Experimental Design Materials and Methodsmentioning
confidence: 99%
“…Proteomic studies revealed that BMI was inversely associated with four important omental adipose tissue mitochondrial proteins—citrate synthase, HADHA, LETM1, and mitofilin . A lower abundance of mitochondrial proteins in subcutaneous adipose tissue has been recorded in insulin resistance without the presence of obesity and in visceral fat of individuals with type 2 diabetes .…”
Section: Mitochondrial Metabolism In White At In Health and In Obesitymentioning
confidence: 99%
“…In 2015, Lindinger et al published the first mitoproteomics study on this area [ 152 ]. Despite the limitations of their analysis (e.g., only 62 putative mitochondrial proteins were identified), the authors validated four proteins (citrate synthase, mitofilin, HADHA, and LETM1) that were inversely associated with body mass index (BMI) in white adipocyte mitochondria from 76 patients.…”
Section: Addressing Mitochondrial Dysfunction Through High-throughmentioning
confidence: 99%